(3GdCLhHI GdSQjI Yf GdCdZGR GdLRQjIs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s ((3Ydj Hf CMeO Hf Ydj Hf YHOGddg GdMfHdj GdfGHdSj s)
(3ChdgG (B:s
(3hHYO abO hQO aj gPG GdReGf eG oJeJMf Hg GdCPgGf hojYQa Hg GdEfSGf ef GdMjhGf s
(3BNQgG (B:s
(3acf NGWHkG jfLM eQGec YfOgG aCbOe JaR hCMeO Edgc s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs